Iron deprivation restrains the differentiation and pathogenicity of T helper 17 cell. Issue 6 (6th October 2021) - Li, Lin; Xia, Yuting; Yuan, Shijie; Li, Fei; Xie, Xiaorong; Luo, Yuan; Yang, Xiang-Ping; He, Ran
Abstract: Iron plays a critical role in immune responses. However, its role in T helper cell differentiation and function remains poorly understood. In this study, it is shown that the restraint of iron availability through blocking CD71-mediated iron endocytosis impaired the differentiation and pathogenicity of TH 17 cells. Administrations of anti-CD71 mAb could relieve the development of experimental autoimmune encephalomyelitis (EAE). Mechanistically, the iron deficiency due to the blocking of CD71 enhanced IL-2 expression, which further restrained the differentiation of TH 17 cells. Meanwhile, CD71 blockade impaired histone modifications of Il17 gene and reduced the recruitment of RORγt to Il17a locus. In sum, the findings reveal that iron plays a pivotal role in regulating TH 17 cell differentiation and function in autoimmune diseases. Graphical Abstract: Blocking iron intake by anti-CD71 mAb impaired the response of TH 17 cells, ameliorating autoimmune disease severity.